2001
DOI: 10.2166/ws.2001.0111
|View full text |Cite
|
Sign up to set email alerts
|

Advanced water treatment system using ozone and ozone resistant microfiltration module

Abstract: In order to achieve an efficient and economical advanced drinking water system, the relationship between operating conditions, membrane filtration flux and water qualities was examined by using a pilot plant consisting of ozonation facility, ozone resistant microfiltration (MF) module and granular activated carbon (GAC) tower. It was found that keeping residual ozone of more than 0.3 mg/L on the membrane surface is necessary in order to obtain a high membrane filtration flux. Withy ozone dosage of 3 mg/L by ej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Fouling Reduction. Preoxidation has been found to be effective in reducing organic fouling of LPMs; ozone seems to be a promising preoxidant for this purpose as found in several studies (76,78,79). A recent pilot-scale study also showed that a combination of 0.5 mg/L of permanganate and 1 mg/L of chlorine significantly reduced the fouling of a UF membrane in an integrated coagulation-UF system during the treatment of a reservoir water impaired by algae (80).…”
Section: Preoxidationmentioning
confidence: 91%
“…Fouling Reduction. Preoxidation has been found to be effective in reducing organic fouling of LPMs; ozone seems to be a promising preoxidant for this purpose as found in several studies (76,78,79). A recent pilot-scale study also showed that a combination of 0.5 mg/L of permanganate and 1 mg/L of chlorine significantly reduced the fouling of a UF membrane in an integrated coagulation-UF system during the treatment of a reservoir water impaired by algae (80).…”
Section: Preoxidationmentioning
confidence: 91%
“…(2016) [1][2][3][4][5][6][7][8] www.deswater.com doi: 10.1080/19443994.2016.1180266 Bench-scale work has shown that preozonation can remove dissolved organic foulants such as humic substances that are known to cause chemically irreversible membrane fouling [6][7][8]. However, since most of this work has considered preozonation application directly ahead of the membrane process, work has been limited to ozone-tolerant ceramic membranes [9][10][11][12].…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Hashino et al [3] tested an ozone-resistant polyvinylidene fluoride microfiltration membrane for treatment of surface water. In their pilotscale work, ozone was applied directly ahead of the membrane process so that a residual of 0.3 mg L −1 O 3 was detectable immediately upstream of the membrane surface.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that biological treatment goals could be satisfied to a large degree while simultaneously meeting other drinking water treatment objectives such as disinfection and particle removal. In order to achieve an efficient and economical advanced drinking water system, the relationship between operating conditions, membrane filtration flux and water qualities was examined by using a pilot plant consisting of ozonation facility, microfiltration (MF) module and granular activated carbon (GAC) tower (Hashino et al, 2001). It was found that keeping residual ozone of more than 0.3 mg/L on the membrane surface was necessary to obtain a high membrane filtration flux.…”
Section: Disinfection Methodsmentioning
confidence: 99%